An integrated overview of metadata in ATLAS - Gallas, E; Malon, D; Hawkings, R; Albrand, S; Torrence, E (2010)
Metadata (data about data) arise in many contexts, from many diverse sources, and at many levels in ATLAS. Familiar examples include run-level, luminosity-block-level, and event-level metadata, and, related to processing and organization, dataset-level and file-level metadata, but these categories are neither exhaustive nor orthogonal. Some metadata are known a priori, in advance of data taking or simulation; other metadata are known only after processing, and occasionally, quite late (e.g., detector status or quality updates that may appear after initial reconstruction is complete). Metadata that may seem relevant only internally to the distributed computing infrastructure under ordinary conditions may become relevant to physics analysis under error conditions ("What can I discover about data I failed to process?"). This talk provides an overview of metadata and metadata handling in ATLAS, and describes ongoing work to deliver integrated metadata services in support of physics analysis. © 2010 IOP Publishing Ltd.